Lived experiences with inclusive education from the perspective of a pupil with visual impairment and his mother—a case study - Hovorková, Lenka; Horňáčková, Zuzana; Belkin, Liliana; Růžičková, Veronika; Přibylová, Tereza; Kantor, Jiří (Frontiers in Education, 2025)
In 2016, there was an important legislative change toward inclusive education (IE) in the Czech Republic, affecting students with different types of Special Educational Needs (SEN) such as visual impairment (VI). As no prior research has investigated the experiences of IE for Czech pupils with VI and their parents, we conducted this phenomenological case study to understand the experiences of a boy with VI and his mother in relation to IE at primary school. Methods: The case study was based on Van Manen's methodology, using semi-structured interviews and thematic analysis. The results (eight themes) show the importance of family support and parental engagement, which helped to overcome some of the education system's shortcomings (e.g., the teacher's unwillingness to cooperate with the family). However, the mother expressed fears about her son's education as he gets older. The boy experienced satisfaction with his education and was proud of his achievements thus far. The case study showed that pupils with VI and their parents may face specific barriers associated with the availability of assistive technologies for VI, and limited provision of support for self-care and orientation. Importantly, these barriers may extend to students with other types of SEN, such as limited awareness of appropriate teaching strategies for pupils with SEN or challenging attitudes of teachers. Involving parents in the educational process may serve as a strategy to overcome these barriers and facilitate inclusion in mainstream settings.